Analisa Unjuk Kerja Flap Sebagai Penambah Koefisien Gaya Angkat - Rifdian I. S. (Jurnal Penelitian)
The process of takeoff and landing is a crucial factor in the phase of flight, other than because it is on the critical height but also the critical speed. At the time of the landing process required a low speed (no stall), as well as providing a high braking effect is obtained for a smooth landing and sliding distance is relatively short. At that result, in the process of landing a maximum flap deflection is used to produce CLmax and drag the highest. At the time the plane accelerate speeds for takeoff, immediately attempted to get the low takeoff speed (no stall), as well as provide a small braking effect to immediately achieved a high rate of speed. Thus required a small flap deflection of flaps on takeoff position.